(untitled) (African Journal of Biomedical Research, 2019)
Adolescent sexual activities present health risks which can lead to negative reproductive health outcomes. This study assessed knowledge of, attitude to, sexual coercion experiences of, and confidence in adopting safer sex methods among in-school rural adolescents in Akute, Ogun State, Nigeria. This was a descriptive cross-sectional study (279 in-school adolescents ;108 males and 171 females). Knowledge attitude and practise questionnaire (Interviewer-administered) was used to assess socio-demographic characteristics, sexual coercion experiences and safer sex behaviour adopted. Frequencies was described and bivariate analysis between socio-demographic factors and adolescents’ sexual behaviour was calculated at p<0.05. Respondents mean age was 13±2.4 years with majority being female. About 71% of the respondents who had prior sexual experience had an unplanned sexual debut and 64% have more than one sexual partner. About 84% of the respondents reported adopting abstinence as a safe method of sexual activity. About one-third learnt about sex from their peers and through social media. Gender, age, level of education, family type, place of residence and parents’ occupation were significantly associated with respondent’s sexual behaviour. It can be concluded from this study that at least one out of every four in-school adolescents in Akute, Ogun State is sexually active and most likely to engage in unsafe sexual practices.